POLA ASUH ORANG TUA KELAS MENENGAH DALAM MEMBANGUN PERILAKU SOSIAL ANAK USIA REMAJA - Apriani, Reni; Widiansyah, Subhan; Lindawati, Yustika Irfani (Universitas Tanjungpura, 2022)
The purpose of this study is to describe and analyze in-depth about parenting patterns in building social behavior of adolescents in Banjarsari Subdistrict Cipocok Jaya Serang City. The research conducted is qualitative field research, where this research produces analytical procedures that do not use statistical analysis procedures or other quantification methods.The method used in this study is a descriptive method. Data collection techniques are conducted among others: interviews, observations and documentation. Interviews are conducted on parents and children. Observations are carried out to see the parenting patterns given to the child. And documentation is done in order to obtain information and written sources or documents when conducting research.Parenting Patterns in Adolescent Social Behavior Development In Banjarsari Village, Cipocok Jaya District, Serang City, no parents are involved in raising their children, and only one parenting pattern is used in educating and caring for them.